Spatially Directed Functionalization by Co-electropolymerization of Two 3, 4-ethylenedioxythiophene Derivatives on Microelectrodes within an Array. Issue 16 (15th December 2020) - Jones, Benjamin J.; Korzeniewski, Carol; Franco, Jefferson H.; Minteer, Shelley D.; Fritsch, Ingrid
Abstract : Electrodeposited conductive copolymer films with predictable relative properties (quantities of functional groups for further modification and capacitance) are of interest in sensors, organic electronic materials and energy applications. Potentiodynamic copolymerization of films in aqueous solutions of two different thiophene derivatives, (2, 3-dihydrothieno[3, 4-b]dioxin-2-yl)methanol (1 ) and 4-((2, 3-dihydrothieno[3, 4-b][1, 4]dioxin-2-yl)-methoxy)-4-oxobutanoic acid (2 ), containing 0.02 M total monomer (0, 25, 34, 50, 66, 75, 100 mol% 2), 0.05 M sodium dodecyl sulfate, and 0.1 M LiClO4, on gold microelectrodes in an array was investigated. Decreasing monomer deposited ( m) from 0 to 100 mol% 2 is attributed to a decreasing pH that inhibits electropolymerization. Molar ratios of 1 and 2 in the films, determined by micro-attenuated total reflectance Fourier transform infrared spectroscopy and X-ray photoelectron spectroscopy, tracks closely with the ratio in the deposition solutions. Capacitances measured from cyclic voltammetry in aqueous buffer and electron transfer of ferrocyanide at the films are unaffected by copolymer composition, except for the 100 mol% 2 case. Ratios of reverse-to-forward faradaic peak currents suggest that films with high content of 1 expand in the anodic form and contract in the cathodic form and vice versa for films with high content of 2, where anions and cations dominate counterion transport from solution, respectively.